1999
DOI: 10.1007/s003359900983
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome searches for quantitative trait loci controlling blood pressure and related traits in four segregating populations derived from Dahl hypertensive rats

Abstract: The Dahl salt-sensitive rat is one of the principal animal models of hereditary hypertension. Genome-wide searches were undertaken to detect quantitative trait loci (QTLs) that influence blood pressure, cardiac mass, and body weight in four F2 populations derived from Dahl salt-sensitive rats and different inbred normotensive control strains of rat. We detected three QTLs associated with one or more of the phenotypes, using a stringent statistical criterion for linkage (p < 0.00003). These included a novel QTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 41 publications
3
31
1
Order By: Relevance
“…Our objective for this study was to use substitution mapping to further delimit this RNO3 BP QTL-containing region, narrowing the interval used to identify candidate genes for future study. Another RNO3 q-terminal BP QTL was also identified using a salt-loaded F 2 (S 3 BN) population, although in contrast 1 with our results, overdominance was observed at this BP QTL (Kato et al 1999).…”
contrasting
confidence: 67%
“…Our objective for this study was to use substitution mapping to further delimit this RNO3 BP QTL-containing region, narrowing the interval used to identify candidate genes for future study. Another RNO3 q-terminal BP QTL was also identified using a salt-loaded F 2 (S 3 BN) population, although in contrast 1 with our results, overdominance was observed at this BP QTL (Kato et al 1999).…”
contrasting
confidence: 67%
“…The QTL Bw2 colocalizes with a locus associated with body weight in a SS/jrxMNS cross. 22 The position of the locus Cmi1 coincides almost exactly with a QTL linked to aortic weight in a SS/jrxSHR cross 23 and a congenic interval associated with both blood pressure and heart weight in a SS/jrϫLew strain combination. 24 It is, however, nearly 100 cM distal to a QTL linked to cardiac mass in a SSϫSHR cross 25 Along the same line, previous studies have consistently shown the implication of QTL on chromosome 1 for the control of body weight, heart weight, and cardiac mass index in different rat crosses primarily designed to investigate the genetic control of complex disorders, including type 1 diabetes, type 2 diabetes, and hypertension.…”
Section: Discussionmentioning
confidence: 74%
“…No linkage of insulin, uric acid, FFA, or adiposity was reported for these two genomic regions; however, their importance is further supported by the overlapping findings of linkage of other metabolic syndrome-related traits. So, the region between D3Rat37 and D3Rat257 has been linked to glucose levels after pancreatectomy (30), body weight (14), cardiac mass (7,27), and heart rate (24), whereas loci within the more telomeric part of RNO3 were reported to influence variation of blood pressure, kidney mass (27), and urine albumin level (48). One of the possible candidate genes present in the region is a paired homeodomain transcription factor Pax6, a key regulator of pancreatic islet hormone gene transcription required for normal islet development (38).…”
Section: Genetic Architecture Of the Metabolic Syndromementioning
confidence: 99%